Rotational surfaces with Cheng-Yau operator in Galilean 3-spaces - Kelleci, Alev (Hacettepe Univ, Fac Sci, 2021)
In this paper, we study three types of rotational surfaces in Galilean 3-spaces. We classify rotational surfaces satisfying L(1)G = F(G + C) for some constant vector C is an element of G(3) and smooth function F, where L-1 denotes the Cheng-Yau operator.
Keywords: L-1-pointwise 1-type; Cheng-Yau operator; rotational surface; Galilean spaces